Energetic and nutrient metabolizability values of corn obtained with nutritional corrections for broilers - Letícia Makiyama; Renata Ribeiro Alvarenga; Paulo Borges Rodrigues; Márcio Gilberto Zangeronimo; Evelyn Cristina de Oliveira; Verônica Maria Pereira Bernardino; Antônio Amandio Pinto Garcia Júnior; Antônio Gilberto Bertechini (Revista Brasileira de Zootecnia, 2012)
The experiment was carried out to evaluate the influence of nutritional correction on the partial diet replacement or pure-food methodology to determine the energy values (apparent metabolizable energy - AME and nitrogen-correct apparent metabolizable energy - AMEn) and coefficient of metabolizability of nutrients of maize. The method of total excreta collection was used, with 120 female Cobb 500® broilers weighing 1,339±3 g and at 28 days of age distributed in a completely randomized design with five replicates and four birds per experimental unit. The treatments were pure maize with three levels of nutritional correction (0, 50 and 100%) and a maize-replaced basal diet (400 g/kg) with two levels of correction (0 and 100%). The corrections were made in order to meet the nutritional requirements of calcium, available phosphorus and sodium yonder trace minerals, vitamins, choline, lysine, methionine + cystine, threonine and tryptophan. The AME and AMEn of maize and coefficient of metabolizability of dry matter were higher when correction at 100% was made, regardless of the methodology used (pure feed or replaced basal diet). The correction at 50% of nutrients increased the coefficient of metabolizability of crude protein in pure maize when compared with 0 or 100% of correction. The values determined with pure maize were lower than those determined with the method of partial replacement. The absence of nutritional correction underestimates the energy values and metabolizability of nutrients from maize.